2020
DOI: 10.1017/s2045796020000918
|View full text |Cite
|
Sign up to set email alerts
|

The victim-bully cycle of sexual minority school adolescents in China: prevalence and the association of mood problems and coping strategies

Abstract: Aims Compared to their heterosexual peers, youth who identify as lesbian, gay or bisexual (LGB) tend to suffer higher rates of peer victimisation from bullying. However, studies of LGB adolescents' participation as bullies are scarce. We aimed to examine the possible association of sexual minority identity and the heightened risk of not only being bullied but bullying others as well. We also explored the effect of one's sexual identity on their involvement in bullying through the mediation of coping strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 59 publications
2
17
0
6
Order By: Relevance
“…These results indicate that bullying prevalence among sexual minorities may be higher than in university or work settings. Similarly, other forms of victimisation such as verbal/physical harassment and being treated unfairly due to sexual minority status was also prevalent among LGB students and youth ( 35 36 ). This study indicates that victimisation among the study participants continues to be a significant issue post-secondary education.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that bullying prevalence among sexual minorities may be higher than in university or work settings. Similarly, other forms of victimisation such as verbal/physical harassment and being treated unfairly due to sexual minority status was also prevalent among LGB students and youth ( 35 36 ). This study indicates that victimisation among the study participants continues to be a significant issue post-secondary education.…”
Section: Discussionmentioning
confidence: 99%
“…Gender nonconformity is often perceived as a threat to family values, social norms, and cultural notions of masculinity. With the growing intolerance of sexual and gender diversity in Chinese educational settings in recent years, the situation of lesbian, gay, bisexual, and transgender (LGBT) youth has become even more precarious (Chan et al, 2022; Huang et al, 2018; Wang et al, 2020). To enhance our understanding of the lived experiences of gender-nonconforming youth in China, this study sought to examine the association of gender nonconformity with peer victimization and internalizing problems in Chinese educational settings and investigate the moderating effects of perceptions of a structured and supportive school climate.…”
Section: Effects Of Peer Victimization On Gender-nonconforming Youthmentioning
confidence: 99%
“…In addition, it has been demonstrated that stigma-related victimization persists throughout the life-course for many sexual minorities, and this is associated with poor mental health outcomes (i.e. depressive symptoms) [28,29]. It is possible that victimization is attributed to an established stressful atmosphere, which consequently generates adverse mental health outcomes [30,31].…”
Section: Discussionmentioning
confidence: 99%